(3GdUfGYI GdUZjQI dLGdjfhSs - (3LGdjfhSs
(3ChdgG (B:s
(3bGd LGdjfhS (B: (3cd GdJYGdje GdJi JLQi Ydi JQJjH , aEf GdeSGdc ajgG Ydi KdGKI CfMGA CMOgG jchf Ydi WQjb GdYcS hGdJMdj hgh Gf jbje GdTF GdPi jbUO Edjg s
(3BNQgG (B:s
(3dCf ef QCjj CMUjgG cdgG ai ebGdI hGMOI Gh ebGdJjf hGLYd Pdc YfhGf GdcJH dLGdjfhS aj PcQ cJHg Je cJGH GdUfGYg GdUZjQg dLGdjfhS fbd oMfjf Hf ESMGb hGdMeO hGdefg ddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3GdfSNI HgG MhGTs
(3hgh GdcJGH GdKGfi ef LhGeY GdcJH GdSJI YTQ dLGdjfhS GdJj cGfJ JbQC Ydi GdoeYdejf HGdEScfOQjIs
(3bhHdJ HCUdjf SfI (B692s
(3hHgGeTgG JUMjMGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdKGfi (B- (3U (B144 s
Keywords: (3GdWHs